Association of Pretreatment Anemia with Pathological Response and Survival of Breast Cancer Patients Treated with Neoadjuvant Chemotherapy: A Population-Based Study. - Wenjie Zhu; Binghe Xu (PLoS ONE, 2015)
Anemia related to adjuvant chemotherapy might predict compromised survival in patients with breast cancer. The present population-based study was to investigate the correlation of pretreatment anemia with pathological response and long-term prognosis of breast cancer patients receiving neoadjuvant chemotherapy (NCT).From 1999 to 2011, a total of 655 patients with operable or locally advanced breast cancer who underwent NCT before definitive surgery were reviewed. The patients were subdivided into anemic (baseline hemoglobin (Hb)<12.0 g/dL) and non-anemic (Hb≥12.0 g/dL) groups. Comparison was made between anemic and non-anemic groups concerning the rate of pathological complete response (pCR), relapse-free survival (RFS), overall survival (OS) and cancer-specific survival (CSS). Logistic and Cox regression models were utilized to determine the predictive value of pretreatment anemia in outcomes of patients undergoing NCT.166 women (25.3%) were anemic before treatment. Patients in the anemic group were less likely to achieve pCR in NCT than their non-anemic counterparts (odds ratio (OR) 0.428, 95% confidence interval (CI) 0.198-0.927, p = 0.031). Patients with baseline anemia displayed inferior 10-year RFS (59.1% vs 66.0%, p = 0.022 by log-rank), OS (75.3% vs 90.9%, p<0.001) and CSS (82.4% vs 94.4%, p<0.001) compared with those without. After adjustment for confounders, pretreatment anemia was demonstrated to correlate with elevated risk of relapse (hazard ratio (HR) 1.453, 95% CI 1.077-1.962, p = 0.015), cancer-specific mortality (HR 2.961, 95% CI 1.679-5.222, p<0.001) and all-cause mortality (HR 2.873, 95% CI 1.757-4.699, p<0.001).Pretreatment anemia was associated with worse pathological response to NCT as well as survival status in breast cancer. Further studies are warranted to identify optimal interventions and improve the prognosis of this subgroup.